Pendapatan Usahatani Wortel Di Desa Surbakti, Kecamatan Simpang Empat, Kabupaten Karo - Kusbiantoro, Dedi; Nasution, Khairunnisyah; Hendrawan, Dian; Asbur , Yenny; Purwaningrum, Yuyuk (Poltanesa, 2022)
Carrots are a superior agricultural product in Surbakti Village it self. With these conditions, Surbakti village has great potential in terms of agriculture, especially carrots. However, at this time the carrot farmers in Surbakti Village are faced with a problem, namely the productivity of carrots has not been maximized and the price of carrots is uncertain, it will affect the productivity and income obtained by farmers. This study aims to analyze the income of carrot farming. The research was conducted in August 2022. Data analysis used income analysis and R/C ratio analysis. The average income of carrot farming in Surbakti Village, Simpang Empat District, Karo Regency is Rp. 14,996,308.4/ha/MT. The average total cost incurred in carrot farming activities is Rp. 11,439,494,68/ha/MT, and the average revenue for carrot farming is Rp. 26,435,803.5/ha/MT. This means that carrot farming in Surbakti Village, Simpang Empat District, Karo Regency is still profitable because farmers' income can still cover the total costs incurred during the carrot farming production process. Keywords: Income, Farming, Carrots, Revenue, Production Costs.